THE EFFECT OF INFRASTRUCTURE MANAGEMENT, WORK ETHIC, AND COMPENSATION ON EMPLOYEE PERFORMANCE OF JULI PUBLIC HEALTH CENTER, JULI DISTRICT, BIREUN REGENCY - Em Yusuf Iis; Lola Amelia Sari Br.S.Pane; Nurmala; Yusniar (RADJA PUBLIKA, 2025)
The purpose of this study is to analyze the influence of infrastructure management, work ethic, and compensation on employee performance at Juli Health Center, Juli District, Bireun Regency. The research method used is a quantitative approach with a survey, where data were collected through questionnaires and analyzed using SEM PLS analysis with the help of the Smart PLS application. The results of the analysis revealed that infrastructure management has a positive and significant effect on employee performance, work ethic has a positive and significant effect on employee performance, and compensation has a positive and significant effect on employee performance. These findings indicate that infrastructure management, work ethic, and compensation are factors that can improve employee performance both in facing work challenges and completing a job.